2017
DOI: 10.1038/cdd.2017.163
|View full text |Cite
|
Sign up to set email alerts
|

p53 shades of Hippo

Abstract: The three p53 family members, p53, p63 and p73, are structurally similar and share many biochemical activities. Yet, along with their common fundamental role in protecting genomic fidelity, each has acquired distinct functions related to diverse cell autonomous and non-autonomous processes. Similar to the p53 family, the Hippo signaling pathway impacts a multitude of cellular processes, spanning from cell cycle and metabolism to development and tumor suppression. The core Hippo module consists of the tumor-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 187 publications
4
65
0
3
Order By: Relevance
“…However, this mechanism has not been thoroughly investigated in human keratinocytes. Given that, 1) the biological functions of p53 and the Hippo pathway overlap at multiple levels and their upstream cues remain largely unknown (Furth et al, 2018); 2) the Hippo pathway is required in E-cadherin mediated contact inhibition of proliferation (CIP) in dense cell populations (Kim et al, 2011) and as we and others have shown that Dsg3 engages in cross talk with E-cadherin and regulates its adhesive function (Rotzer et al, 2015;Tsang et al, 2010;Tsang et al, 2012b), we decided to analyse the Hippo pathway and its downstream effector, YAP (Furth et al, 2018). First, we analysed, by Western blotting, the expression of YAP, as well as pYAP-S127 (an indicator of the Hippo pathway (Piccolo et al, 2014)), alongside p53 in confluent NTERT cells with and without Dsg3 knockdown and subjected the cells to equiaxial cyclic strain (the experiment as described above).…”
Section: Dsg3 Forms a Complex With Yap And Regulates Yap Functionmentioning
confidence: 99%
“…However, this mechanism has not been thoroughly investigated in human keratinocytes. Given that, 1) the biological functions of p53 and the Hippo pathway overlap at multiple levels and their upstream cues remain largely unknown (Furth et al, 2018); 2) the Hippo pathway is required in E-cadherin mediated contact inhibition of proliferation (CIP) in dense cell populations (Kim et al, 2011) and as we and others have shown that Dsg3 engages in cross talk with E-cadherin and regulates its adhesive function (Rotzer et al, 2015;Tsang et al, 2010;Tsang et al, 2012b), we decided to analyse the Hippo pathway and its downstream effector, YAP (Furth et al, 2018). First, we analysed, by Western blotting, the expression of YAP, as well as pYAP-S127 (an indicator of the Hippo pathway (Piccolo et al, 2014)), alongside p53 in confluent NTERT cells with and without Dsg3 knockdown and subjected the cells to equiaxial cyclic strain (the experiment as described above).…”
Section: Dsg3 Forms a Complex With Yap And Regulates Yap Functionmentioning
confidence: 99%
“…Activation of p53-mediated transcription by various stress signals results in the expression of a number of pathways that accomplish diverse phenotypes that include cell cycle arrest, 3 senescence, apoptosis and other types of cell death, metabolic alterations, DNA repair processes, and other prosurvival mechanisms and tumor suppression (reviewed in refs. [3][4][5][6][7]. There is an active debate about which p53-regulated genes and pathways are responsible for the tumor suppressor phenotype.…”
mentioning
confidence: 99%
“…5,6 The answer to this question may reside in a better understanding of how stress activates the p53 protein and how a particular stress initiates a transcriptional pathway resulting in an improved fidelity in the process of cellular replication. 7 P53-regulated gene products interact with many other signal transduction pathways involved in metabolism and growth (PI3K-mTOR pathways), stem cells (the Wnt pathway), and development affecting the p53-Hippo pathways, 7 the immune system, the fidelity of epigenetic signals, senescence, aging and life span, or death (reviewed in Wu and Prives 8 ). It appears that p53-mediated functions are involved from early development, through life, and in death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a via Hippo também está relacionada às metástases ósseas do câncer de mama pela ativação de YAP/TAZ em células tumorais (Rashidian et al, 2015;Li et al, 2017). Várias linhas de evidência sugerem que a deleção ou mutação de LATS1/2 leva a um fenótipo de câncer de mama mais agressivo, com maior capacidade invasiva (Visser e Yang, 2010;Maugeri-Sacca e De Maria, 2016;Li et al, 2017;Furth et al, 2018;Wei et al, 2018) e evidências têm sugerido que um dos pontos importantes para a ativação da via Hippo são perturbações homeostáticas relacionadas à privação de substratos energéticos (Mao et al, 2015;Ardestani et al, 2018;Furth et al, 2018).…”
Section: Microambiente Tumoralunclassified